THE ROLE OF SHARIA ECONOMICS IN REALIZING GOLD INDONESIA 2045 - Muhamad Abdul Rohman Rosid; Dian Febriyanti (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
Backgrounds Researchers believe that the Islamic economy can have a strong contribution in supporting the creation of a Golden Indonesia 2045 with the potential for Indonesia to have the largest Muslim population in the world and a business sector that has greater growth potential. Objectives Therefore, this research aims to analyze the role of Sharia Economics in Realizing Golden Indonesia 2045. Methods: This research is qualitative research with a descriptive approach, namely describing the role of Sharia Economics in supporting the creation of a Golden Indonesia 2045 Results and Conclusions: The economy is getting serious attention with the potential for the largest Muslim population in the world. Due to the role of sharia economics in supporting the creation of a Golden Indonesia 2045 which is measured by per capita income which is equivalent to the per capita income of developed Indonesia and the poverty rate which is at 0.6% -0.8%, increasing Indonesia's position on SGIE with these six indicators will help Achieving a Golden Indonesia is based on the assumption that increasing the sharia financial market can increase employee income in the sharia financial sector, increasing the lifestyle and halal food market can increase employment opportunities and income levels.